Pengembangan Instrumen Assesmen HOTS Pada Pembelajaran IPA Kelas V Sekolah Dasar - Deden Dicky Dermawan; Sri Wardani; Yuli Kurniawati S Pranoto Kurniawati S Pranoto (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to produce a Higher Order Thinking Skill (HOTS) assessment instrument for grade 5 elementary school in science learning theme 8 The environment of our friends that is valid, reliable, and feasible. This research method uses R&D research with ADDIE research design (analysis, design, development, implementation, and evaluation). The steps developed include design, expert validation, limited-scale trials, and large-scale trials. The data collection technique in this development research is a test technique (multiple choice). The results of the validation of the HOTS multiple-choice test instrument are valid, the reliability value during the limited-scale trial is 0.648 and when the wide-scale test is 0.762 the value indicates a reliable instrument, the results of the HOTS assessment of the research instrument can be concluded that it has met the criteria of being valid, reliable, and feasible to use.